Physical training of 30–40 years old tourists skiers to ski sports hiking - Топорков Олександр Миколайович (Alexander Toporkov) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: compare the test results obtained at different stages of physical training of tourists skiers, immediately after passing of the ski sports hiking of the third category of complexity and 14 days after hiking. Determine the effectiveness of the designed program to improve the physical readiness of 30–40 years old tourists skiers. Material and Methods: 14 people aged 30 to 40 years old who have a different experience in water, hiking and mountain as well as ski-sport hiking took part in research. Analysis of scientific and methodical literature, pedagogical observations, pedagogical experiment, methods of mathematical statistics is used. Results: the test results of 30–40 years old tourists skiers which are the participants in the experimental group received at different stages of preparation and preparatory period and the results after passing ski sports hiking of the third category of complexity are processed. Their comparative analysis is held. Conclusions: it was found that the developed training program can effectively influence the physical readiness of tourists skiers, as well as all functions and systems that contribute to the successful passage of ski sports categorized hike